Engineering yeast for producing human glycoproteins: where are we now?. (January 2015) - Laukens, Bram; Visscher, Charlotte De; Callewaert, Nico
ABSTRACT : Yeast has advanced as an alternative for mammalian cell culture for the production of recombinant therapeutic glycoproteins. Engineered yeast strains not only allow to mimic the human N-glycosylation pathway but also specific types of human O-glycosylation. This is of great value for therapeutic protein production and indispensable to determine the structure-function relationships of glycans on recombinant proteins. However, as the technology matures, some limitations have come up that may hamper biomedical applications and must be considered to exploit the full potential of the unprecedented glycan homogeneity obtained on relevant biopharmaceuticals. In this special report, we focus on the recent developments in N- and O-glycosylation engineering in yeasts of industrial importance, to produce recombinant therapeutics with customized glycans.